Students’ Learning Obstacles and Alternative Solution in Counting Rules Learning Levels Senior High School - M A Jatmiko; T Herman; J A Dahlan (Universitas Sebelas Maret, 2017)
The counting rules is a topic in mathematics senior high school. In the learning process, teachers often find students who have difficulties in learning this topic. Knowing the characteristics of students' learning difficulties and analyzing the causes is important for the teacher, as an effort in trying to reflect the learning process and as a reference in constructing alternative learning solutions which appropriate to anticipate students’ learning obstacles. This study uses qualitative methods and involves 70 students of class XII as research subjects. The data collection techniques used in this study is diagnostic test instrument about learning difficulties in counting rules, observation, and interview. The data used to know the learning difficulties experienced by students, the causes of learning difficulties, and to develop alternative learning solutions. From the results of data analysis, the results of diagnostic tests researcher found some obstacles faced by students, such as students get confused in describing the definition, students difficulties in understanding the procedure of solving multiplication rules. Based on those problems, researcher analyzed the causes of these difficulties and make hypothetical learning trajectory as an alternative solution in counting rules learning.